EPIDEMIOLOGY LENSES : A PRESENTATION - Prakash V. Kotecha (Indian Association of Preventive and Social Medicine, 2010)
The presentation started with his nostalgic memory with Professor NR Mehta, Professor DH Trivedi and Professor AK Niyogi with whom he had the opportunity to work as a student and then as a colleague. He refreshed his memory as warden of Dr. Jivraj Mehta Hall where his predecessors were Prof NR Mehta and Professor DH Trivedi and he remembered to be the first time examiner with Prof. Niyogi who was examiner with him for the last time in his career .....